MEDIATION ANALYSIS: ISSUES AND RECOMMENDATIONS - Memon, Mumtaz Ali; Cheah, Jun-Hwa; Ramayah, T.; Ting, Hiram; Chuah, Francis (Journal of Applied Structural Equation Modelling, 2018)
This editorial outlines and responds to some of the most frequently asked questions regarding mediation analysis. Specifically, six key issues are addressed with reference to the state-of-theart mediation literature. In doing this, we provide practical guidelines for researchers to successfully conceptualize, test and interpret mediation models. Recent references are also provided to discourage researchers from using outdated mediation approaches in their theses/manuscripts. It is our hope that this effort will clarify misconceptions regarding mediation analysis and provide up-to-date guidelines for researchers to make informed decisions and conduct the analysis appropriately.